Exploring the Potential of Plumbagin as an Activator of Caspase 3 for Non-small Cell Lung Carcinoma: A Comprehensive in silico Study - Mohd Saeed; Non-Small Cell-Lung Cancer (NSCLC) Caspase-3, Plumbagin, BOILED EGG Plot analysis, ADMET/Tox, Molecular docking, MD simulation
Caspase-3 regulates apoptosis, and its deregulation in Non-Small Cell-Lung Carcinoma (NSCLC), and contributes to tumour growth and therapeutic resistance. Significant resistance to chemotherapy and radiation therapy, which are two frequently used treatment modalities for lung cancer, is linked to the decreased activity of caspase-3 in NSCLC. Preclinical and early clinical investigations, for example, have shown potential for targeting specific biochemical pathways involved in caspase-3 regulation, such as the Bcl-2 family of proteins or the Inhibitor of Apoptosis Proteins (IAPs). However, this study investigates the activation potential of plumbagin, a potential naphthoquinone, towards Caspase-3, which in turn targets the progression of NSCLC. The potential of naphthoquinones has already been explored and experimentally validated by several researchers in cancer-targeted drug discovery-based studies. This study focuses on exploring the physicochemical and ADMET properties of plumbagin prior to molecular docking. This renders the binding energy of the plumbagin-caspase-3 docked complex at -10.13 kcal/ mol. Further, MD simulations validated the potential of Plumbagin to serve as a promising target for drug discovery against caspase-3 by analysing the computed trajectories. Given that naphthoquinones are preferred drug candidates, discovering natural chemicals that act as caspase-3 activator is a key step towards developing viable drugs for NSCLC.